The gender dimension of economic globalization : an annotated bibliography - Thorin, María (CEPAL SantiagoCL, 2003)
Provides a comprehensive compilation and catergorization of resources on the topic of gender and economic globalization. Highlights the literature on Latin American and Caribbean women